2007
DOI: 10.1523/jneurosci.0779-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor and TrkB Modulate Visual Experience-Dependent Refinement of Neuronal Pathways in Retina

Abstract: Sensory experience refines neuronal structure and functionality. The visual system has proved to be a productive model system to study this plasticity. In the neonatal retina, the dendritic arbors of a large proportion of ganglion cells are diffuse in the inner plexiform layer. With maturation, many of these arbors become monolaminated. Visual deprivation suppresses this remodeling. Little is known of the molecular mechanisms controlling maturational and experience-dependent refinement. Here, we tested the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
134
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(143 citation statements)
references
References 63 publications
(109 reference statements)
8
134
1
Order By: Relevance
“…RGCs with dendrites in both the ON and OFF layers of the IPL in young retinas appeared to shift to a single IPL layer with development. That ON-OFF RGCs decrease after eye opening is evident by physiology and morphology in other studies as well (Cantrell et al 2010;Landi et al 2007;Liu et al 2007;Tian and Copenhagen 2003). Thus, some ON and OFF cells detected at P30 likely would not have been detected from the same retina at eye opening, when they were ON-OFF responsive.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…RGCs with dendrites in both the ON and OFF layers of the IPL in young retinas appeared to shift to a single IPL layer with development. That ON-OFF RGCs decrease after eye opening is evident by physiology and morphology in other studies as well (Cantrell et al 2010;Landi et al 2007;Liu et al 2007;Tian and Copenhagen 2003). Thus, some ON and OFF cells detected at P30 likely would not have been detected from the same retina at eye opening, when they were ON-OFF responsive.…”
Section: Discussionsupporting
confidence: 57%
“…This classification is when the RGC dendrites are viewed in the plane of the retina. These dendrites, however, are dynamic in the vertical plane, shifting layers within the IPL after eye opening (Liu et al 2007;Xu and Tian 2007).…”
Section: Discussionmentioning
confidence: 99%
“…1998), and BDNF signaling modulates maturation of TH-immunoreactive amacrine cells (Liu et al, 2007). Dopaminergic input has been suggested to contribute to RGC receptive field organization in animals (for review, see Witkovsky, 2004).…”
Section: Role Of Dopaminergic Amacrine Cells In Retinal Maturation Inmentioning
confidence: 99%
“…Dopaminergic amacrine cells express BDNF receptor TrkB and are sensitive to BDNF (Cellerino and Kohler, 1997;Cellerino et al, 1998;Lee et al, 2005;Liu et al, 2007;Loeliger et al, 2008). Dopamine levels in the retina affect RGC receptive fields (for review, see Witkovsky, 2004), possibly contributing to retinal spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Its promoter and regulatory elements have been used to generate several Six3-cre transgenic mouse lines (Furuta et al, 2000). Many of these cre transgenes are able to mediate deletion of a floxed gene in the hypothalamus and the retina (Furuta et al, 2000;Liu et al, 2007). We found that one of the reported lines, #69 (termed Six3-cre#69 here), was also able to mediate gene deletion in layer 4 of sensory cortical areas.…”
mentioning
confidence: 92%